Investigation on Cell Surface Markers of Dental Pulp Stem Cell Isolated from Impacted Third Molar Based on International Society for Cellular Therapy Proposed Mesenchymal Stem Cell Markers - Ferry Sandra; Janti Sudiono; Yohanna Feter; Nadhia Sari Afiana; Jessica Nathalia Chandra; Kharima Abdullah; Jasmine Shafira; Angliana Chouw (Cell and BioPharmaceutical Institute, 2019)
Background: Recently we have isolated and cultured dental pulp stem cell (DPSC) derived from impacted third molar (DPSC-M3). The DPSC-M3 was suggested as mesenchymal stem cell, however the cell surface markers were not completely clarified. Therefore current study was conducted to investigate the markers.Materials and Methods: Passage 5 DPSC-M3 was cultured, labeled and examined with flow cytometer. All markers were investigated according to the proposed cell surface marker panel for the minimal identification of human mesenchymal stem cell (MSC) by International Society for Cellular Therapy (ISCT). The positive markers were cluster of differentiation (CD)90, CD73, CD105, while the negative markers were CD34, CD45, CD11b, CD19, and Human Leukocyte Antigen (HLA)-DR. Results: Results showed that the size and granularity of DPSC-M3 were ranged from 75 to 230 and 27 to 203, respectively. The cell surface antigens examination showed that CD90, CD105 and CD73 were highly expressed (>95%), meanwhile expressions of CD45, CD34, CD11b, CD19 and HLA-DR were <2%.Conclusion: Since the all markers expression were in accordance to the proposed cell surface marker panel for the minimal identification of human MSC by ISCT, DPSC-M3 could be suggested as an MSC.Keywords: dental pulp, stem cell, dental pulp stem cell, ISCT, flow cytometry